Association between high polygenic risk scores and long-term exposure to air pollution in asthma development: a hospital-based case-control study - I-Chieh Chen; Yi-Ming Chen; Yun-Wen Chen; Tzu-Hung Hsiao; Hui-Wen Yang; Kuo-Tung Tang; Ching-Heng Lin; Yu-Wen Chu (Environmental Health)
Abstract Background Air pollution is widely associated with allergic diseases, including asthma. Although previous studies have suggested an epidemiological link between air pollution and asthma, the combined effects of air pollutants and polygenic risk scores (PRSs) on asthma risk remain incompletely understood. This study aimed to examine the impact of air pollutants and PRS on asthma risk among patients in a Taiwan medical institution. Methods This retrospective matched case-control study utilized data from the Taiwan Precision Medicine Initiative (TPMI) project to compare asthma patients with a non-asthmatic control group. Participants were stratified into quartiles based on their asthma PRS, while air pollutant exposure was assessed by both duration and concentration. Conducted at Taichung Veterans General Hospital, the study followed participants from January 1, 2000, to December 31, 2021. Logistic regression was used to analyze the relationships between air pollution exposure, genetic risk, and asthma incidence. Results A total of 9,756 participants were included (3,252 asthma patients and 6,504 controls). Individuals in the highest PRS quartile demonstrated a significantly increased asthma risk (odds ratio = 1.532, 95% CI = 1.333–1.762, p < 0.0001). Long-term exposure to low levels of PM2.5, PM10, NO2, Mn, and O3 further elevated asthma risk, with the association becoming more pronounced under conditions of high air pollution. Conclusion Long-term exposure to low concentrations of air pollutants significantly increases asthma risk, especially among individuals with high genetic susceptibility. These findings emphasize the importance of personalized health management for individuals with elevated PRS. Trial registration Not applicable.